Disease Status–Dependent Drug–Herb Interactions: NASH Lowered the Risk of Hepatotoxicity in Rats Coadministered With Simvastatin and Gardenia jasminoides J. Ellis - Li, Ziwei; Lyu, Yuanfeng; Zhao, Jiajia; Li, Dan; Lin, Zhixiu; To, Kenneth Kin Wah; Yan, Xiaoyu; Zuo, Zhong (Frontiers in Pharmacology, 2021)
Concurrent use of simvastatin (SV) and Gardenia jasminoides J.Ellis (GJ) was adopted in patients with multimorbidity such as stroke rehabilitation patients with NASH. Although hepatotoxicity has been reported in both of them and NASH could alter the pharmacokinetics of drugs/herbs, the interaction between SV and GJ and the related hepatotoxicity remained uninvestigated under neither healthy nor NASH condition. The current study aims to evaluate the potential hepatotoxicity resulted from the interactions between SV and GJ in both healthy and NASH rats. Both healthy and NASH rats received two-weeks SV (p.o., 8.66 mg/kg, once daily) and/or GJ (p.o., 325 mg/kg, twice daily). Pharmacokinetic profiles of SV, simvastatin acid (SVA, active metabolite of SV) and geniposide (major component in GJ), hepatic Cyp2c11/Oatp1b2/P-gp expression, biomarker levels of liver function and lipid levels and liver histology were compared to demonstrate the interactions in rats. To explore the mechanism of the interaction-mediated hepatotoxicity, hepatic genipin-protein adduct content and iNOS/COX-1/COX-2 expressions from related groups were compared. Moreover, liver histology of healthy/NASH rats at 90 days after discontinuation of two-weeks GJ in absence and presence of SV were evaluated to estimate the long-term impact of the interactions. GJ reduced the systemic exposures of SV and SVA by up-regulating the hepatic P-gp expression in healthy but not NASH rats. Meanwhile, SV increased the systemic exposure of geniposide via inhibiting the activity of P-gp in both healthy and NASH rats. Although neither SV nor GJ induced hepatotoxicity in healthy rats, their co-treatment elevated serum ALT and AST levels, which may attribute to the aggravated genipin-protein adduct formation, inflammation infiltration and iNOS/COX-1 expressions in the liver. In NASH rats, SV and/or GJ reduced serum ALT, AST, LDL/vLDL and TC levels via alleviating hepatic inflammation infiltration and iNOS/COX-1 expressions. Moreover, in comparison to NASH rats, more severe fibrosis was observed in the livers of healthy rats at 90 days after discontinuation of two-weeks SV and GJ co-administration. Although interactions between SV and GJ induced short-term and long-term liver injury in healthy rats, NASH condition in rats could lower such risk.